Novel equal area law and analytical charge-electric potential criticality for charged Anti-de Sitter black holes - Run Zhou; Shao-Wen Wei (Physics Letters B, 2019)
We study the equal area law and charge-electric potential criticality for the charged Anti-de Sitter black holes. Considering that the black hole charge is a double-valued function of the electric potential, we investigate the equal area law in detail. We find that the equal area law has two different expressions when the thermodynamic quantities are near the critical point and far from the critical point. For these two different cases, we obtain the analytical coexistence curve for the low and high electric potential black hole phases by using these two expressions of the equal area law. Based on the result, we analytically study the phase diagram and the critical phenomena in the charge-electric potential plane. Keywords: Black holes, Thermodynamic phase transition, Equal area law